The Function Of Teacher Organizations In Improving Teacher Discipline And Professionalism - Vidya Daniati; Saskia Melandari; Abdurrahmansyah Abdurrahmansyah (Peneliti.net, 2026)
Teacher organizations have an important role in improving the quality of human resources in the field of education, particularly in building teachers’ discipline and professionalism. This study aims to analyze the function of teacher organizations in improving work discipline and teacher professionalism in carrying out their duties and responsibilities. This research uses a qualitative approach with a descriptive method. Data collection techniques were conducted through observation, interviews, and documentation involving teachers and teacher organization administrators. The results show that teacher organizations function as a forum for guidance, competency development, and as a means of communication and collaboration among teachers. Through activities such as training, seminars, scientific discussions, and professional ethics development, teacher organizations are able to increase teachers’ awareness of the importance of discipline in carrying out their duties and improve their professional competence. In addition, teacher organizations also play a role in instilling values of responsibility, professional commitment, and improving teachers’ pedagogical and professional abilities.